Nursery grounds of the commercially important shrimp Farfantepenaeus brasiliensis (Latreille, 1817) (Decapoda, Penaeoidea): Comparison of the population structure between two periods - De Sousa, Aline Nonato [UNESP]; Bernardes, Veronica Pereira [UNESP]; Hiroki, Kátia Aparecida Nunes [UNESP]; De Almeida, Ariádine Cristine [UNESP]; Teixeira, Gustavo Monteiro [UNESP]; Fransozo, Adilson [UNESP] (My University, 2019)
This study compared the population structure of Farfantepenaeus brasiliensis in two distinct periods in Fortaleza Bay, southeastern Brazil. Individuals were monthly sampled in November 1988-October 1989 (period 1) and in November 2008-October 2009 (period 2). In period 1, 80 juveniles were found (36 males and 44 females), whereas in period 2 were found 226 juveniles (62 males and 164 females). The individuals from period 2 were smaller (males: 17.0 ± 3.0 mm; females: 16.4 ± 3.3 mm) than those from period 1 (males: 22.1 ± 6.4 mm; females: 21.7 ± 6.3 mm). This reduction in body size throughout the study period might have been a consequence of an improper conservation management in the area up to 2008. In both sampling periods, the recruitment occurred in summer; however, in period 2, there was a higher abundance of juveniles in autumn too. This might be related to a higher precipitation caused by the El Niño South Oscillation (ENSO) in 2009. The increased precipitation might have prolonged the reproductive period and, consequently, the recruitment.
Keywords: Environmental protection area; Fishing; Pink shrimp; Recruitment; Ubatuba